Advancing Evidence‐Based Practice Through Implementation Science: Critical Contributions of Doctor of Nursing Practice‐ and Doctor of Philosophy‐Prepared Nurses. - McNett, Molly; Masciola, Randee; Sievert, Deana; Tucker, Sharon (Worldviews on Evidence-Based Nursing (John Wiley & Sons, Inc.), 2021)
Purpose: Describe the evolution of implementation science and the roles and potential collaborations of doctorally prepared nurses to advance implementation science in practice settings. Methods: Review of academic preparation and areas of expertise for doctorally prepared nurses as it relates to implementation science and evidence‐based practice (EBP). Findings: There have been substantial gains in the number of academic programs in healthcare that include content on EBP, resulting in healthcare teams that are motivated to align practices with best evidence. Unfortunately, many EBP initiatives stall during early stages of implementation, resulting in fragmented practices and persistent gaps between evidence and practice. Implementation science aims to bridge this gap and provides a structured, science‐based approach to implementation. Few healthcare teams are familiar with implementation science, and many do not incorporate knowledge from the field when implementing EBPs. Doctorally prepared nurses are in a unique position to serve as leaders in EBP implementation due to the breadth and depth of academic preparation and their pivotal roles across practice settings. Conclusions: Collaboratively aligning existing strengths of PhD and DNP prepared nurses with knowledge of implementation science can advance implementation of EBP across practice settings to effectively incorporate and sustain meaningful change to improve outcomes. Linking Evidence to Action section: Doctorally prepared nurses are in a unique position to advance and apply the science of implementation in practice settings. Nurse scientists can generate evidence on effective strategies and outcomes among healthcare teams to successfully integrate evidence based practices into routine care. Nurse leaders and educators can apply these findings and use an implementation science approach when leading clinical teams in evidence‐based practice changes.